(untitled) (Indian Journal of Arid Horticulture, 2025)
Pomegranate (Punica granatum L.) is the important crop of arid and semi-arid regions of India. Maharashtra is the leading state for area and production of pomegranate followed by Karnataka and Andhra Pradesh. At present, Maharashtra occupies about 92,000 ha area out of 1.3 lakh ha area available under pomegranate in India. In pomegranate, genetic base is very narrow. Therefore, creation of variability is utmost important need for crop improvement programme. Attempts have been made earlier to induce mutation in pomegranate by treating seeds with gamma rays (5-20 kR) and various forms were obtained with desirable traits. However, the dwarf mutation forms were most commonly observed in pomegranate (Akhund- zade-IM. 1979 and Levin, 1990). Gamma irradiation as a breeding tool to create variability in both horticulture and field crops was reported by several workers (Haskins and Chapman, 1956; Mikaelsen, 1968 and Pathak, 2003). Several released varieties of field and fruit crops have been enlisted which were developed through gamma irradiation (Anon., 1981). Considering the significance of gamma irradiation in crop improvement, the present study was under taken and response of gamma irradiation on seed germination and subsequent survival of seedlings of pomegranate was studied.